The Relationship of Increasing Food Production to Social Welfare and Health - Ahmad Syaekhu; Tenri Sau; Sri Handayani; Irma Irma (Jurnal Penelitian Pendidikan IPA, 2023)
The threat of an economic recession in 2023 raises concerns. Farmers, as the main supporters of food production, also feel that rice, the main food of the Indonesian people, must always be available in sufficient quantities. The population explosion during the pandemic was caused by high birth rates. Population growth must coincide with adequate food security so that there will be no famine and other chaos as a follow-up impact. The success of farmers in increasing agricultural output should be enjoyed in the form of social welfare and health. This study aims to see the relationship between increasing food production and social welfare and health. This research uses quantitative methods. Data collection using questionnaires Analysis of the study's results using linear regression It was found that there was a significant relationship between increased food production and farmers' social welfare and health. This research can be a reference for continuing to increase food production through the opening of new agricultural land. Another option is to reduce the conversion of agricultural land into settlements or offices. Thus, farmers have the opportunity to continue to maintain their food production numbers